On a Volterra Stieltjes integral equation. (1990) - Vaz, P. T.; Deo, S. G.
Abstract : The paper deals with a study of linear Volterra integral equations involving Lebesgue-Stieltjes integrals in two independent variables. The authors prove an existence theorem using the Banach fixed-point principle. An explicit example is also considered.